Hydrothermally Synthesis and Characterization of Lanthanide Coordination Polymers with (42.62.82)(43.63)2(46.67.82)(48.67) Topology [Ln2(1,4-pda)3(H2O)]·2H2On (Ln = Pr, Nd, Dy) - Zhang, Mei-Li; Gao, Na; Gao, Lou-Jun; Han, Xu-Hua; Chen, Xiao-Li (Asian Journal of Chemistry, 2015)
Three 3D lanthanide coordination polymers [Ln2(1,4-pda)3(H2O)]·2H2On (1,4-pda = 1,4-phenylenediacetic acid, Ln = Pr for 1, Nd for 2 and Dy for 3) have been hydrothermally synthesized and characterized by elemental analysis, IR spectroscopy, thermogravimetric analyses and single-crystal X-ray diffraction techniques. The structure indicates that three complexes have similar structures and belong to monoclinic crystal system, P21/c space group. In which, trans-bis(μ2-h2:h1) and trans-bis(μ2-h1:h1) 1,4-pda2- anions link the Ln(III) center to generate a 2D network, furthermore, the dimensionality is extended to a (4,6)-connected 3D architecture with a Schläfli symbol of (42.62.82)(43.63)2(46.67.82)(48.67) through same coordination mode 1,4-pda2- anions linking. In additional, photoluminescence properties of three complexes have also been studied. (CCDC 1009612 for 1, 1009613 for 2 and 1009614 for 3).